Genomic adaptation of flowering‐time genes during the expansion of rice cultivation area. (21st April 2018) - Itoh, Hironori; Wada, Kaede C.; Sakai, Hiroaki; Shibasaki, Kyohei; Fukuoka, Shuichi; Wu, Jianzhong; Yonemaru, Jun‐ichi; Yano, Masahiro; Izawa, Takeshi
Summary: The diversification of flowering time in response to natural environments is critical for the spread of crops to diverse geographic regions. In contrast with recent advances in understanding the molecular basis of photoperiodic flowering in rice ( Oryza sativa ), little is known about how flowering‐time diversification is structured within rice subspecies. By analyzing genome sequencing data and a set of 429 chromosome segment substitution lines (CSSLs) originating from 10 diverse rice accessions with wide distributions, we revealed diverse effects of allelic variations for common flowering‐time quantitative trait loci in the recipient's background. Although functional variations associated with a few loci corresponded to standing variations among subspecies, the identified functional nucleotide polymorphisms occurred recently after rice subgroup differentiation, indicating that the functional diversity of flowering‐time gene sequences was not particularly associated with phylogenetic relationship between rice subspecies. Intensive analysis of the Hd1 genomic region identified the signature of an early introgression of the Hd1 with key mutation(s) in aus and temperate japonica accessions. Our data suggested that, after such key introgressions, new mutations were selected and accelerated the flowering‐time diversity within subspecies during the expansion of rice cultivation area. This finding may imply that new genome‐wide changes for flowering‐time adaptation are one of the critical determinants for establishing genomic architecture of local rice subgroups. In‐depth analyses of various rice genomes coupling with the genetically confirmed phenotypic changes in a large set of CSSLs enabled us to demonstrate how rice genome dynamics has coordinated with the adaptation of cultivated rice during the expansion of cultivation area. Significance Statement: This work comprehensively identified functional nucleotide polymorphisms in flowering‐time genes from various rice genomes through phylogenetic analyses combined with genetically confirmed phenotypic changes by a large set of chromosome segment substitution lines. Our data indicate that a specific introgression and subsequent accumulation of newly occurring mutations greatly contributed to genetic improvement of photoperiodic flowering for northward expansion of rice cultivation area.